Personality of gymnasts and coping strategies to manage stress - Kaplanova, A. (Science of Gymnastics Journal, 2019)
The reason why some gymnasts give an excellent performance and others are barely able to give average performance in competition may be embedded in the sphere of personality structure. Stress is the body's response to the imbalance between the demands of the external environment and the body's ability to meet those requirements. Therefore, the aim of our study is to investigate the relationship between personality structure of gymnasts and coping strategies to manage stress. The study sample consisted of 56 elite Slovak gymnasts (16 men and 40 women) aged from 15 to 26, with an average age of 19.34 ± 3.15 years. The personality structure of gymnasts was investigated by the NEO-FFI inventory (Ruisel & Halama, 2007). Coping strategies to manage stress were investigated by the Athletic Coping Skills Inventory ACSI-28 (Smith et al., 1995). The correlational research design was used. The results of our study showed that 6 of the 7 subscales of coping strategies to manage stress are in relation to personality structure of the gymnasts, namely emotional lability/stability, extroversion/introversion and openness to experience. We also found that none of subscales of coping strategies to manage stress is in relationship to an agreeableness and conscientiousness of gymnasts. A better understanding of the personality traits and coping strategies to manage stress may help coaches and sports psychologists to develop effective interventions and assist gymnasts to attain optimal performances in competition.